About certain classes of limiting laws - Mišeikis, F. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ф. Мишейкис. О некоторых классах законов распределения F. Mišeikis. Apie kai kurias pasiskirstymo dėsnių klases